DEVELOPING LINGUISTIC COMPETENCE IN PRIMARY SCHOOL STUDENTS REGARDING PARTS OF SPEECH - Rasulova Sanobar (Web of Journals Publishing, 2025)
This article is about the issue of developing the linguistic competence of primary school students in terms of adjective vocabulary in their native language classes, as well as the methods used to form linguistic competence in the adjective vocabulary of primary school students. provides theoretical information and analyzes these methods.
Keywords: Competence, linguistic competence, linguistic analysis, phonetics, quality, grammatical analysis.